The Relationship Between Parents' Understanding in Fine Motor Development and Giving Stimulation Skills to Children - Dwi Fahira Utari; Vevi Sunarti (Universitas Negeri Padang, 2021)
This research is motivated by the low level of stimulus given by parents to children around the Tabing Indah Housing Market, Pasar Baru, Bayang District, Pesisir Selatan Regency, this is presumably because parents' understanding of children's fine motor development is relatively low. This study aims to: 1) describe parents' understanding of fine motor development; 2) describe the provision of stimulus to children; and 3) looking at the relationship between parents' understanding of fine motor development and providing stimulus to children around the Tabing Indah Housing Market, Bayang District, Pesisir Selatan Regency. This type of research is quantitative research with correlational descriptive technique. The population in this study were parents of children around Tabing Indah Housing, Bayang District, Pesisir Selatan Regency as many as 20 people and a sample of 14 people. The data collection technique is in the form of a questionnaire with a data collection tool in the form of a questionnaire. The data analysis technique used the Spearman rho proportion and correlation formula. The results showed that: (1) parents' understanding of fine motor development was low, (2) giving children a low stimulus, (3) there was a significant relationship between parents' understanding of fine motor development and providing stimulus to children around Tabing. Beautiful Housing Market. Bayangan Baru District, Pesisir Selatan Regency. It is recommended that parents increase knowledge about the effect of stimulation on children's fine motor development so that their development is maximized.